Exposure to stress across the life course and its association with anxiety and depressive symptoms: Results from the Australian Women's Wellness After Cancer Program (WWACP). (November 2017) - Seib, Charrlotte; McCarthy, Alexandra; McGuire, Amanda; Porter-Steele, Janine; Balaam, Sarah; Ware, Robert S.; Anderson, Debra
Highlights: While greater life stress is generally linked with more anxiety and depressive symptoms, the timing of stressors may also be an important factor. In this study anxiety scores were higher in women with early life stressors. This study highlights the need for whole-of-life supportive care approaches for women previously treated for cancer. Supportive care approaches should include targeted strategies for effective management of stress, anxiety and depression. Abstract: Objectives: Earlier life stressors can increase the risk of persistent anxiety and depressive symptoms in women after cancer, though our understanding of the underlying mechanisms is limited. In this study, we tested alternative life course models to determine which best described associations between exposure to stressors in childhood, adolescence, and adulthood, and self-reported health in women previously treated for breast, gynaecological, and blood cancer. Study design: Data were drawn from 351 Australian women within 2 years of completing active cancer treatment who were participating in the Women's Wellness After Cancer Program (WWACP) randomised controlled trial. A model-building framework compared "accumulative risk" and "sensitive period" stress exposure hypotheses with the saturated model to determine best fit. Main outcome measures: Symptoms of anxiety and depression were measured using the Center for Epidemiologic Studies Depression Scale (CES-D) and the Zung Self-rating Anxiety Scale (SAS). Results: Participants with the greatest number of stressful life events (SLEs) reported higher anxiety scores and more depressive symptoms. Alternative life course models for psychological distress (measured through the CES-D and SAS) and stress were compared with the saturated model (i.e., the accumulative risk). The more restrictive "sensitive period" models were the best fit for depressive symptoms though none was significantly better than another. In contrast, an "early sensitive" model provided the best fit for anxiety data. Conclusions: Anxiety scores were higher in women with early life stressors. This study highlights the need for whole-of-life supportive care approaches for women previously treated for cancer, which should include targeted strategies for effective management of stress, anxiety and depression.